(untitled) (Świat Idei i Polityki, 2002)
The paper deals with comparative analysis of the two historic moments in which cosmopolitism was a certain recipe for life. The moments were distinct from each other of about 2500 years, but with some common characteristic features. The question concerns Asia Minor in the 4,h and 3rd centuries B.C. and the Old Continent of the late years of 2O'h century. The matter regards the Hellenic world based on the idea of Alexander the Great and the united Europe based on Shuman’s idea. Despite a large difference in time, astonishing historical and ideological similarities may help not only to analyze the present reality but also to forecast the future of the European community structure which is now being created. According to the author, the contemporary European countries have to decide fast what political form the integrated organism in statu nascendi may assume. Otherwise, the countries will share the fate of Hellenic world, a beautiful stoic blow of cosmopolitism that finished very fast and suddenly.